Internet Giants and Unfair Tax Practices - Ayrault, Ludovic (Law, State and Telecommunications Review, 2018)
Purpose ”“The article analyzes the issue of unfair tax practices of the big Internet companies. The companies use several unfair but legal means to avoid taxation and compliance to national tax law. The text addresses two types of tax loopholes: tax nexus and tax base erosion. Given this, the text shows some responses to struggles against the unfair the tax practices. Methodology/approach/design ”“ The article draws its analyses from the French statutory and case law in comparison to international sources, such as the OCDE (Organization for Economic Co-operation and Development) and sovereign jurisdictions, notably Ireland and the United States of America. In addition, the article uses French and international reports. Findings ”“ Concerning the legal loopholes, it is shown that the “territorial element” and “transfer value” figure as the main concepts for the tax evasion debate. In relation to the ways of fighting unfair practices, there are the fight against compliant tax jurisdictions and the requirement of business transparency by means of imposing information disclosure obligations. Practical implications ”“ It is possible to clarify the tax behavior adopted by Internet giants, as well as the possible ways (and its difficulties) of coping with these unfair practices in the European context. Originality ”“ This paper originality lies on the fact that it discusses the unfair tax behavior of large Internet corporations and looks for ways to curb them.